Tissue Amino Acid Flux After Exposure of Rats to Diplococcus pneumoniae - Wannemacher, R. W. (1971)
The concentration of 21 individual free amino acids in serum, liver, and skeletal muscle was determined in rats during the incubation, acute illness, and terminal stages of experimental infection with Diplococcus pneumoniae. By 4 hr after subcutaneous inoculation with bacteria, the concentration of total and many individual free amino acids in serum, liver, and muscle was significantly decreased in comparison to findings in noninfected, pair-fed control rats. By use of a nonmetabolizable amino acid analogue (cycloleucine), it was possible to detect a flux of amino acids from muscle to liver in the infected rat. The endogenous amino acids which moved to the liver were rapidly utilized for the synthesis of serum proteins.